ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI JAGUNG HIBRIDA DI DESA MODO KECAMATAN BUKAL KABUPATEN BUOL - Ahmad Z. A. Purwanto; Hj. Hadayani; Abdul Muis (Universitas Tadulako, 2015)
This research was conducted in Modo village, Bukal sub-district, Buol regency. The location was selected purposively based on that this village has produced the highest cornyield among villages in the sub district. The research took place since August to October 2015. The sample was all population members including 55 respondents. Primary and secondary data were collected and analyzed using Cobb-Douglas production function analysis to determine the relation between variables studied. The dependent variables included land, seed, fertilizer, and labor(X) whereas the dependent variable was corn production (Y). The results of this research showed that land, seed, fertilizer, and labor significantly affect the hybrid corn farm production in Modo village. The average costs incurred is IDR 7,387,839/1.18 ha equal toIDR 6,260,881/ha, while the income of the farming obtained is IDR 13,372,500/1.18 ha equal toIDR 11,332,627/ha, and the respondent income is IDR 5,984,661/1.18 ha equal to IDR 4,071,746/ha.Keywords: Income, Hybrid Corn Farm, Production.